The Role of Classroom Teachers in Preventing Bullying Behavior at the Elementary School Level - Yuliyanti (Aisha Edutama, 2024)
One of the most important components of education is teachers, considering that teachers are the spearhead of the national education system. One of the problems that teachers often experience is bullying behavior carried out by students, especially in science learning. Bullying is an act of violence carried out by groups or individuals that can hurt other people verbally, physically or psychologically. Bullying behavior is a form of abuse behavior that usually occurs in the school environment. This research is motivated by a phenomenon that schools or educational institutions are considered to be a boomerang for some students. because in the world of education, students experience a lot of violent behavior and this is considered normal or trivial. The role of teachers is very much needed, apart from educating and teaching teachers must also take preventive action against problems caused by bullying. The aim of this research is to find out the role of teachers in preventing bullying behavior at the elementary school level. This research method is literature study research with data collection using reading journals, reviewing relevant literature, reading and taking notes and managing previous research materials. Based on previous research that has been reviewed from 3 journals and 10 relevant theses, it is stated that the role of teachers in dealing with bullying varies between each teacher. The results of the analysis show that teachers play a very important role in anticipating cases of bullying in elementary schools, namely by guiding, advising, directing, developing and providing examples of good attitudes at school.